(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This research sets a focus on developing an IT-based Jire collaborative learning model device for teaching physics in senior high schools. This is development research using a 4-D design model proposed by Thiagarajan, Semmel, and Semmel. The model comprises four stages, i.e., define, design, develop, and disseminate. The results manifest that (1) the IT-based Jire collaborative learning model device for the momentum and impulse materials is valid and reliable to use in the learning process, (2) the IT-based Jire collaborative learning model is practical to use in the learning process and effective to escalate students’ responses to physics, particularly the momentum and impulse materials. Additionally, learning implemented using the Jire collaborative learning is considered good, and (3) the IT-based Jire collaborative learning model is efficient to enhance students’ learning activities and outputs, where based on my observation, the students’ activity percentage is 90% above. The percentage of the students’ learning outputs is 80-100%. The result is indicative of the validity, practicality, and effectiveness of the IT-based Jire collaborative learning model in physics learning, principally the momentum and impulse materials.